(untitled) (gjstudies, 2020)
This research presents a novel, multi-layered computational framework for forensicaccounting, designed specifically to address the escalating complexity of modern financial crimes. Moving beyond traditional ledger analysis and established data miningtechniques, the proposed methodology integrates three unconventional computationalparadigms: a modified Cellular Automaton model for simulating the emergent, selforganizing behavior of illicit financial networks; an application of Ant Colony Optimization algorithms, repurposed from swarm intelligence, to trace obfuscated transactionpathways that evade standard graph-theoretic analyses; and a semantic topology mapping technique, adapted from digital humanities, to deconstruct and visualize the narrative structures within fraudulent corporate communications and regulatory filings. Thecore research question investigates whether such a hybrid, cross-disciplinary computational approach can identify latent fraud patterns and actor relationships that remaininvisible to both conventional auditing and current forensic software. A prototypesystem, the Forensic Accounting Computational Toolkit (FACT), was developed andtested against a synthesized, multi-jurisdictional financial crime dataset incorporatingelements of trade-based money laundering, cryptocurrency layering, and fraudulentasset valuation. Results demonstrate that the Cellular Automaton model successfullyidentified 34% more potential collusion clusters than standard community detectionalgorithms, while the Ant Colony Optimization tracer revealed 28% longer obfuscationchains. The semantic topology maps provided actionable intelligence on the rhetoricalstrategies of concealment, correlating strongly with areas of high transactional anomaly.The study concludes that the deliberate importation of methodologies from seeminglydisparate fields—complex systems theory, bio-inspired computing, and narrative analysis—offers a significant and original advancement in forensic accounting capability.This approach redefines the investigative target from discrete fraudulent entries to theunderlying adaptive systems and communicative acts that constitute complex financialcrime, providing investigators with a more powerful lens for detection and attribution.